Juridical Analysis of the Legal Liability of Human Smuggling Perpetrators According to Law Number 6 Of 2011 Concerning Immigration (Case Study: Decision Number 684/Pid.Sus/2025/PN Mdn) - Siboro, Rini Oktavia; Simamora, Janpatar; Situmorang, Samuel F.B (Journal of Law, Politic and Humanities, 2026)
Human smuggling is an immigration-related criminal offense that has serious impacts on state sovereignty and legal order. Although it has been explicitly regulated in Law Number 6 of 2011 concerning Immigration, the enforcement of this law still faces various challenges, particularly regarding the legal liability of perpetrators and judicial considerations in assessing the fulfillment of criminal elements, especially when the perpetrator is an Indonesian citizen. This research aims to analyze the legal liability of perpetrators who transport people across national borders without using valid travel documents and to examine the legal basis of judicial considerations in Decision Number 684/Pid.Sus/2025/PN Mdn. The method used in this research is normative legal research with statutory and case approaches. The results of this study indicate that legal liability can be imposed if all elements of Article 120 paragraph (1) of the Immigration Law are fulfilled, including the element of intent and the act of transporting people across national borders illegally. Judicial considerations are based on the proof of intent, the active role of the perpetrator, and the commission of acts outside the immigration inspection mechanism, so that the decision reflects efforts to protect state sovereignty and prevent human smuggling.